DEVELOPMENT OF NEW TYPES OF VEGETABLE JUICES AND BEVERAGES TECHNOLOGY - Zuxriddin, Vaqqosov; Hakimov, Sardorbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
In this article, vegetables such as cucumbers, carrots, and cabbage are given in different amounts The effect of enzymes such as Pectomaserin, Pectinex Ultra SP-L, Pectomaserin G10X, Fructozyme M and increased juice output in juice production. The effect of the type of vegetables was determined, it was studied the development of original technologies of cucumber, carrot, cabbage juices and drinks.